Associations between genetic and epigenetic variations in cytokine genes and mild persistent breast pain in women following breast cancer surgery. (November 2017) - Stephens, Kimberly E.; Levine, Jon D.; Aouizerat, Bradley E.; Paul, Steven M.; Abrams, Gary; Conley, Yvette P.; Miaskowski, Christine
Highlights: IL6, CXCL8, and TNF are associated with mild persistent breast pain. CpG methylation in the TNF promoter may contribute to mild persistent breast pain. These genetic and epigenetic variations may help to identify high risk patients. Abstract: Persistent pain following breast cancer surgery is a significant problem. Both inherited and acquired mechanisms of inflammation appear to play a role in the development and maintenance of persistent pain. In this longitudinal study, growth mixture modeling was used to identify persistent breast pain phenotypes based on pain assessments obtained prior to and monthly for 6 months following breast cancer surgery. Associations between the "no pain" and "mild pain" phenotypes and single nucleotide polymorphisms (SNPs) spanning 15 cytokine genes were evaluated. The methylation status of the CpG sites found in the promoters of genes associated with pain group membership was determined using bisulfite sequencing. In the multivariate analysis, three SNPs (i.e., interleukin 6 ( IL6 ) rs2069840, C-X-C motif chemokine ligand 8 ( CXCL8 ) rs4073, tumor necrosis factor ( TNF ) rs1800610) and two TNF CpG sites (i.e., c.−350C, c.−344C) were associated with pain group membership. These findings suggest that variations in IL6, CXCL8, and TNF are associated with the development and maintenance of mild persistent breast pain. CpG methylation within the TNF promoter may provide an additional mechanism through which TNF alters the risk for mild persistent breast pain after breast cancer surgery. These genetic and epigenetic variations may help to identify individuals who are predisposed to the development of mild levels of persistent breast pain following breast cancer surgery.